Impact of Workplace Stress on Nursing during the Pandemic: Challenges and Intervention Strategies for Mental Health - Acuña , Mercedes del Carmen; Castillo Benites , Ruth (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Job stress is a response to demands that exceed the adaptive capacity of the individual, with implications for physical and psychological health. In the field of nursing, recognized as a highly stressful profession, work factors are aggravated by conditions such as excessive workload, organizational conflicts and, more recently, by the COVID-19 pandemic. National and international studies highlight the emotional and physical overload of health professionals, showing a negative impact on their well-being and performance. Methods: Several studies have addressed work stress in nursing, using quantitative, qualitative and mixed methodologies to identify stressors and evaluate their effects. The analyses focused on factors such as lack of resources, uncertainty in the face of emerging pathologies, and psychosocial risks in different geographical contexts. In Argentina, research showed high levels of anxiety, exhaustion and burnout during the pandemic, with factors such as fear of contagion and work overload being predominant. Internationally, physical and psychological disorders associated with stress were reported, including sleep disturbances, depression and emotional difficulties. Conclusions: Job stress in nursing, intensified by the pandemic, evidences the need for structural interventions. Improvements in working conditions, provision of adequate resources, and emotional and psychological support are essential to mitigate its effects. In addition, protective factors such as professional resilience highlight the importance of strengthening organizational support networks. The physical and mental stability of staff is crucial for the effectiveness of health services and to ensure quality care in critical times